Traditional Chinese Medicine Enema Therapy in a Patient With a Confirmed Negative SARS-CoV-2 Test in the Respiratory Tract but Positive in the Intestinal Tract: A Case Report - Yuzhu Dai; Zhiyou Zhao; Huajun Zhou; Dedong Huang; Jianjun Luo; Cunhai Zhang; Qingyong Chen; Xingcan Chen; Yuan Yao; Xiaoxiao Jiang; Jun Cheng (Frontiers in Public Health, 2021)
We report the case of a 43-year-old man who was infected with SARS-CoV-2 in February 2020 and actively cooperated with treatment in the hospital. During the course of treatment, we found that the respiratory SARS-CoV-2 nucleic acid became negative, but remained positive in the intestinal tract. As a result, we adjusted the treatment plan to include traditional Chinese medicine enema treatment. The patient had negative intestinal SARS-CoV-2 nucleic acid test within 4 days, and the subsequent repeated review of intestinal SARS-CoV-2 nucleic acid was negative, and the virus was undetectable. It is suggested that traditional Chinese medicine enema treatment may be helpful to remove the SARS-CoV-2 in the intestines of patients with COVID-19 infection, and may support the treatment of patients with respiratory SARS-CoV-2 nucleic acid negative and positive in the intestinal tract.